2013
DOI: 10.1182/blood-2012-04-424275
|View full text |Cite
|
Sign up to set email alerts
|

Targeting transcription factor SALL4 in acute myeloid leukemia by interrupting its interaction with an epigenetic complex

Abstract: Key Points• The SALL4/NuRD/PTEN pathway is important for acute myeloid leukemogenesis.• Targeting AML can be achieved by blocking the interaction between transcription factor SALL4 and the epigenetic NuRD complex.An exciting recent approach to targeting transcription factors in cancer is to block formation of oncogenic complexes. We investigated whether interfering with the interaction of the transcription factor SALL4, which is critical for leukemic cell survival, and its epigenetic partner complex represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 45 publications
2
65
0
Order By: Relevance
“…Consistently, HDAC inhibitors might be useful for the eradication of SALL4-positive HCC cells through their inhibitory effects on histone deacetylation by NuRD [39]. Encouragingly, a recent study demonstrated the utility of a SALL4-binding peptide to inhibit its binding to phosphatase and tensin homolog deleted on chromosome 10 (PTEN) through interaction with HDAC, thereby targeting leukemia cells [21]. Further studies are required to understand the relationship between SALL4, the NuRD complex, and the maintenance of stemness in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, HDAC inhibitors might be useful for the eradication of SALL4-positive HCC cells through their inhibitory effects on histone deacetylation by NuRD [39]. Encouragingly, a recent study demonstrated the utility of a SALL4-binding peptide to inhibit its binding to phosphatase and tensin homolog deleted on chromosome 10 (PTEN) through interaction with HDAC, thereby targeting leukemia cells [21]. Further studies are required to understand the relationship between SALL4, the NuRD complex, and the maintenance of stemness in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to directly target SALL4 as no studies have investigated the inhibition of its transcription using chemical or other approaches [21]. We therefore re-investigated the interaction networks associated with SALL4, and found that SALL4 activation appeared to induce epigenetic modification (Fig.…”
Section: Sall4 and Hdac Activity In Hpsc-hccmentioning
confidence: 99%
“…Furthermore, interfering with the interaction of SALL4 and its epigenetic partner complex has therapeutic effects in cancer. Gao and colleagues have developed a peptide inhibitor that can compete with SALL4 in interacting with the HDAC complex [65]. They demonstrate that treating SALL4-expressing leukemic cells with this peptide leads to cell death through the reactivation of PTEN.…”
Section: Sall4 As Cancer Biomarker and Targetmentioning
confidence: 98%
“…20 We tested whether this 12-AA SALL4 peptide was effective in targeting the SALL4-PTEN-AKT pathway and resulted in decreased viability of hepatocellular carcinoma cells. When 5 µM or 20 µM of nonmutant SALL4 peptide was added to SNU-398 cells, the number of viable cells was reduced, as compared with SNU-398 cells treated with control mutant peptide and scrambled peptide.…”
Section: Targeting Sall4 By a Novel Peptidementioning
confidence: 99%